Contact Heat Evoked Potentials in China: Normal Values and Reproducibility - Sun, Bo; Wang, Hongfen; Chen, Zhaohui; Cui, Fang; Yang, Fei; Huang, Xusheng (Frontiers in Human Neuroscience, 2022)
Background: Contact heat evoked potentials (CHEPs) is used to diagnose small fiber neuropathy. We established the normal values of CHEPs parameters in Chinese adults, optimized the test technique, and determined its reproducibility. Methods: We recruited 151 healthy adults (80 men; mean age, 37 ± 14 years). CHEPs was performed on the right forearm to determine the optimal number of stimuli, and then conducted at different sites to establish normal values, determine the effects of demographic characteristics and baseline temperature, and assess the short- (30 min) and long-term (1 year) reproducibility. N2 latency/height varied with age and sex, while P2 latency/height and N2–P2 amplitude varied with age. The optimal number of stimuli was three. Results: N2 latency/height (t = 5.45, P < 0.001) and P2 latency/height (χ2 = -4.06, P < 0001) decreased and N2–P2 amplitude (t = -5.01, P < 0.001) and visual analog scale score (χ2 = -5.84, P < 0.001) increased with increased baseline temperature (35°C vs. 32°C). CHEPs parameters did not differ with time (baseline vs. 30 min vs. 1 year). Conclusions: We established normal CHEPs values in Chinese adults. We found that CHEPs parameters changed with baseline temperature and that the short- and long-term test reproducibility were satisfactory.